Biologicals, platelet apoptosis and human diseases: An outlook. Issue 3 (March 2015) - Thushara, R.M.; Hemshekhar, M.; Basappa; Kemparaju, K.; Rangappa, K.S.; Girish, K.S.
Highlights Platelets play a major role in health and disease including heart diseases and cancer. Commonly used biologicals induce increased platelet apoptosis and thrombocytopenia. Increased platelet apoptosis causes excess microparticle formation which is dangerous. Side-effects of biologicals on platelets and the consequences are often neglected. There is a need to overcome side-effects of proapoptotic drugs via auxiliary therapy.